The air of the lyceum at VGIK. Interview with Armen Medvedev. (4th May 2019) - Apostolov, Andrei
ABSTRACT: Part of a special issue devoted to the centenary of the Film Institute VGIK, this interview remembers the role of Nikolai Lebedev (1897–1978) as film historian and one of the initiators of the section of film studies at the Film Institute VGIK From 1931 until his death in 1978 he taught and led the department of film studies at VGIK (since 1940 as professor) and between 1934–1936 and 1955–1956 was rector of the institute. He has taught a great many film scholars who have shaped not only film studies as discipline, but also contributed significantly to the writing of film history. In this interview, Armen Medvedev, who studied under Lebedev and went on to play important roles in the management of cinema, including at Goskino, remembers his student experience with Lebedev. The interview was conducted by Andrei Apostolov, who studied with Medvedev in the department of film studies, where he now also teaches.